MASS SPECTROMETRY-BASED APPROACHES TO CHARACTERIZE MYCOBACTERIUM TUBERCULOSIS - Atavliyeva , S.; Tarlykov , P.; Zholdybayeva , E.; Ramankulov , Ye. (Eurasian Journal of Applied Biotechnology, 2018)
Mass spectrometry has greatly contributed to the study and understanding of the pathogenesis of human tuberculosis. Current methods of mass spectrometry have been rapidly evolving over the past two decades in response to the limitations of early proteomic studies. Modern proteomic research includes protein secretion, activation, degradation, and modifications, since post-translational modifications are an additional step in the evolution of pathogenic mycobacteria that gain virulence. The other application of mass spectrometry is in epidemiological studies of mycobacteria, in particular, determining the genetic spoligotype based on matrix-assisted laser desorption/ionization. This review explores M. tuberculosis studies carried out by mass spectrometry, including proteomic profiling with the shotgun-based approach and targeted proteomics. In addition, the most important post-translational modifications studied by mass spectrometry are described.